Affinity-engineered carbon nanofibers as a scaffold for Na metal anodes. Issue 29 (17th July 2020) - Susca, Alessandro; Liu, Jiapeng; Cui, Jiang; Mubarak, Nauman; Wu, Junxiong; Ihsan-Ul-Haq, Muhammad; Ciucci, Francesco; Kim, Jang-Kyo
Abstract : A scalable scaffold made of carbon nanofibers modified with embedded ZnO nanoparticles as facile nucleation sites for stable plating and stripping of Na is developed, leading to much ameliorated cyclic stability at high current densities. Abstract : Metal anodes possess the potential to disrupt the limits imposed by intercalation compounds and achieve a higher storage density for next-generation rechargeable batteries. This study is dedicated to engineering a scalable scaffold made of carbon nanofibers (CNFs) modified with embedded ZnO nanoparticles as facile nucleation sites for enhanced Na plating performance. The pristine CNF network provides a highly conductive, mechanically stable plating platform while the porous morphology effectively lowers the local current density and the volume fluctuations, delivering 1500 cycles at 1 mA cm −2 . In search of appropriate sodiophilic surface for stable Na plating, the affinities between Na and different substrate materials are analyzed by measuring overpotentials, coulombic efficiencies, and through density functional theory calculations. The ZnO@CNF composite created by in situ incorporation of ZnO nanoparticles offers uniform nucleation and deposition of Na through conversion and alloying reactions, leading to ameliorated cyclic stability at a high current density of 3 mA cm −2 . The Na plating thickness is predicted based on simple electrochemical principles and geometric considerations, corroborating experimental measurements. The affinity-engineered ZnO@CNF anodes deliver more than 1000 h of stable plating/stripping cycles in a symmetric battery configuration by effectively inhibiting the growth of dendrites and Na agglomerates.